Promotion of flu vaccination among healthcare workers in an Italian academic hospital: An experience with tailored web tools. Issue 10 (2nd October 2016) - Conte, Alessandro; Quattrin, Rosanna; Filiputti, Elisa; Cocconi, Roberto; Arnoldo, Luca; Tricarico, Pierfrancesco; Delendi, Mauro; Brusaferro, Silvio
ABSTRACT: Background: Influenza causes significant mortality particularly among the elderly and high-risk groups. Healthcare workers (HCWs) are at risk of occupational exposure due to contact with patients. Aims of this study was to promote flu shot among HCWs through a multimedia campaign in a large North-Eastern Italian Hospital. Methods: The 2013/2014 flu vaccination multimedia campaign addressed to HCWs was developed by maintaining pre-existing tools (letters in pay slip and poster displayed in wards) and creating 4 on-line spots (30") delivered trough the hospital intranet. Campaign effectiveness was assessed in terms of changes in knowledge, attitude and practice comparing data of pre (10 items) and post test (20 items) survey on a randomized sample of HCWs. Results: Response rates were 92.6% (464/501) in pre-test and 83.2% (417/501) in post-test. 93.8% (391/417) of HCWs reported to awareness of the campaign to promote vaccination. Spots were seen by 59.6% (233/391) of HCWs. Some reasons for vaccine denial, "not believing in vaccine efficacy" (34.7% to 14.9%), "not considering flu as a serious problem" (from 24% to 12.6%), "thinking not to get sick" (28.7% to 18.2%) or "being against the vaccine" (32.7% to 21%), showed a statistically significant reduction after the exposure to the campaign. The "intention to get vaccinated in the next year" instead, raised effectively (13.1% to 36.6%). Vaccinated HCWs rate in 2013-2014 season was 7.6% (221/2910), and 5.6% (164/2910) in 2012-2013 (p<0.005). Conclusions : The multimedia campaign succeeded with regard to KAP outcomes, but the vaccination rate is still far from the goal of 90%. Due to their impact, especially on younger age groups, web tools deserve to be better studied as effective approach to convey health information among HCWs.